(Nano)partículas metálicas para diferentes arquiteturas de dispositivos eletroquímicos - Orzari, Luiz Otávio (Universidade Federal de São Carlos, 2024)
In this doctoral thesis, new architectures of electrochemical systems for fuel cells, sensors and biosensors were developed. To this end, various methodologies for adding metallic particles to the surface of the working electrode were explored, following characterizations and investigations into their behavior and subsequent applications in energy efficiency and/or determination of analytes. Firstly, a multifunctional device was developed, exploring the combination of fuel cells with electrochemical sensing, in a single system. To this end, compositions of carbon-supported electrocatalysts were investigated, involving the metals Pd, Ag and Bi. In the ethanol oxidation reaction, the Pd50Ag45Bi05/C catalyst demonstrated interesting behavior and cost-efficiency, being subsequently used for the determination of dopamine in synthetic urine samples. Two analytical curves were obtained for the sensor: one involving the direct oxidation of dopamine from 4.0 to 40 µmol L−1, with a detection limit (LOD) equal to 0.035 µmol L−1; and another, due to the complexation that occurs between catecholamines and metal surfaces, from 0.2 to 1.0 µmol L−1, with a LOD of 0.14 µmol L−1. The second device is an electrochemical sensor and immunosensor, in which Pd nanoparticles were electrodeposited on the surface of the working electrode. To this end, a new conductive carbon black and polyvinyl acetate ink was developed to manufacture the three-electrode system. With the aid of Design of Experiments, the parameters for metal deposition were investigated and the sensor was applied to determine epinephrine in synthetic cerebrospinal fluid samples. Afterwards, the sensor was modified with cysteamine and glutaraldehyde for proper immobilization of Anti--synuclein. The biosensor was then used to construct a calibration curve of -synuclein phosphate buffer, with a linear range between 1.5 and 15 g mL−1 (LOD = 0.13 g mL−1) and in samples of human blood serum, in a linear range of 6.0 and 100.5 g mL−1 (LOD = 1.31 g mL−1), by electrochemical impedance spectroscopy, demonstrating its efficiency in more complex environments. The third system involved the use of Au microflowers electrodeposited on the surface of the previously developed conductive ink, to increase the capacitance response of the material. Design of Experiments was used to optimize the conditions of the self-assembled layers for biosensor modification. Once the best working conditions were defined, non-faradaic electrochemical impedance spectroscopy was used to find a linear range between capacitance and PARK7/DJ-1 concentration, corresponding to the region of 20 to 120 ng mL−1. The LOD obtained for this system was 0.207 ng mL−1. The device was then applied to a fortified synthetic cerebrospinal fluid sample, where it showed attractive responses using the spike and recovery method. Finally, a last device was developedfor the oxidation of ethanol, seeking to combine the properties of Au and Bi to produce a more attractive device for catalytic processes. Full factorial and Doehlert matrix designs were used to find an optimal composition between the metals. An extensive morphological and electrochemical characterization was carried out, seeking to understand the behavior of the conductive ink modified with each of the metals separately, as well as with their mixture. Considered a less efficient catalyst due to its high chemical stability, Au becomes much more efficient in synergy with low concentrations of Bi, but the material does not have complete regeneration of its surface, being more suitable for processes in which current generation must be high in a short space of time.
Metallic (nano)particles for different electrochemical devices architectures
Keywords: Partículas Metálicas; Sensor Eletroquímico; Biossensor Eletroquímico; Célula à Combustível; Planejamento de Experimentos; Eletrodeposição de Metais; Metallic Particles; Electrochemical Sensor; Electrochemical Biosensor; Fuel Cell; Metal Electrodeposition; CIENCIAS EXATAS E DA TERRA::QUIMICA